(3CMcGe GdLYGdI (B((3GdhYO HLGFRI GdehLg ddLeghQ(B) (3ai GdTQjYI GdESdGejI hGdbGfhf GdhVYj (B: s (3OQGS`I ebGQf``I (B/ s - (3UHQj LeYI YHOGddg YKeGfs; (3eMeO TcQj SQhQ (B: s; (3eMeO jhSa Mafj (B: s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb (B- (3LGeYI GdbGgQI(B.s, 2016)
(3Ef ehVhY GdLYGdI (B( (3GdhYO HLGFRI GdehLg ddLeghQ (B) (3ai GdTQjYI GdESdGejI hGdbGfhf GdhVYj OQGSI ebGQfI CUHM ef GdehVhYGJ GdgGeI Ydi eSJhi GdTQYj hGdbGfhfj (B: (3abO bSeJg Edi ebOeI JTJed Ydi CgejJg hCSHGH GNJjGQg hefgL GdHMK hNWJg hbO SQJ ajgG Ydi CSGS JbSje GdehVhY Edi HGH JegjOj hHGHjf hNGJeI hbGFeI HGdeUGOQ hGdeQGLY hgPG ehLR eG Je JaUjdg OGNd GdQSGdI (B: - (3Efg HGdQZe ef eTQhYjI GdLYGdI ai Gdabg GdESdGej hGdbGfhf GdhVYj EdG CfgG ai Gdabg GdESdGej bO Jchf HGdYbO Ch HGdEQGOI GdefaQOI (B: (3CeG ai GdbGfhf ade jfXegG EdG HhUagG JUQakG HGdEQGOI GdefaQOI (B: (3hEf cGf GdbGfhf dG jefY ef GdGJaGb Ydi JMhjd GdGdJRGe HHPd YfGjI Edi GdJRGe HJMbjb fJjLI eG de Jcf eSJMjdI GSJMGdI eWdbg (B. - (3hfXQkG dJRGjO CgejI GdLYGdI (B((3GdhYO HLGFRI(B) (3hGfJTGQ JWHjbJgG aEfg jLH EaQGOgG HJfXje bGfhfj TGed (B. - (3Ef GdehGRfI Hjf CMcGe GdLYGdI ai Gdabg GdESdGej hGdbGfhf GdhVYj jKHJ MbjbI GdJTGHg hGdJcGed Hjf CMcGegeG hCfgeG djS VOjf eJfGaQjf (B. - (3Ef HYV CMcGe GdLYGdI GdJi GLJgO ajgG Ch de jJYQV dgG CFeI Gdabg GdESdGej hYdeGA GdSda de jYO jJdGAe GdCNP HgG eY ebJVjGJ GdYUQ GdMGdj eeG jhLH EYGOI GdfXQ ajgG CNPG HeHOC UdGMjI GdTQjYI GdESdGejI GdZQGA dcd ReGf hecGf hCNPG HbGYOI (B( (3dG jecf JZjjQ GdCMcGe HJZjQ GdReGf (B) (3hef gPg GdCMcGe CMcGe GdYed GdSGHb hGddGMb Ydi UOQ UjZI GdLYGdI (B: (3GdLYd GdEMJjGWj (B: (3hGdLYd Ydi GdHQA (B: (3hJCbjJ GdLYGdI (B: (3hGdLYGdI GdJHQYjI (B: (3hJYLjd GdLYd (B: (3hLhGFR GdSdWGf (B: (3hedcjI GdMbhb GdefTFI Ydi GdYed aj GdhYO HLGFRI (B: (3hGNJjGQ GdeSJMb ddLYd HGdbQYI (B: (3hGdLYGdI GdhgejI (B: (3hGdedJRe HGdfabI ai GdLYGdI (B: (3hGdLhGFR GdJQhjLjI (B: (3hLhGFR GdjfGUjH (B: (3hLhGFR GdeSGHbGJ hZjQ Pdc ef GdCMcGe s
(3CWQhMI (B((3OcJhQGg(B)-(3LGeYI GdbGgQI, (B2016.s
(3HHdjhLQGajG (B: (3UaMGJ (B549- 582s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3GdLYGdI aj GdTQjYI GdESdGejIs; (3GdEQGOI GdefaQOI hYdGbJgG HGdLYGdIs; (3dRhe GdhYOs; (3eTQhYjI GdLYGdIs; (3GdhYO HLGFRIs; (3GdLGYds; (3GdLYds; (3GdLhGFR GdJQhjLjIs; (3GdLYGdI aj GdTQjYI GdESdGejIs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- 2016